1987
DOI: 10.1007/bf00379425
|View full text |Cite
|
Sign up to set email alerts
|

Induced tolerance of neonate Heliothis zea to host plant allelochemicals and carbaryl following incubation of eggs on foliage of Lycopersicon hirsutum f. glabratum

Abstract: Incubation of Heliothis zea (Boddie) eggs on foliage of Lycopersicon hirsutum f. glabratum C.H. Mull (accession PI 134417) results in neonates with elevated levels of tolerance to the toxic effects of PI 134417 foliage attributable to 2-tridecanone found in the glandular trichomes which abound on that foliage. The neonates from such eggs are also shown to have elevated levels of tolerance to the carbamate insecticide carbaryl. Incubation of eggs in an atmosphere containing 2-tridecanone similarly produced elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…(Kennedy 1984;Riskallah et al 1986a,b;Kennedy et al 1987a). 2-Tridecanone evidently induces detoxifying enzymes, probably mixed function oxidases, in Heliothis spp.…”
Section: Known Mechanisms Of Resistancementioning
confidence: 99%
See 3 more Smart Citations
“…(Kennedy 1984;Riskallah et al 1986a,b;Kennedy et al 1987a). 2-Tridecanone evidently induces detoxifying enzymes, probably mixed function oxidases, in Heliothis spp.…”
Section: Known Mechanisms Of Resistancementioning
confidence: 99%
“…has been reported in all of these plant species. In many cases, however, resistance factors are present in the foliage (e.g., Farrar and Kennedy 1987a;this Vol.). Heliothis spp.…”
Section: Caterpillars (Lepidoptera)mentioning
confidence: 99%
See 2 more Smart Citations
“…Kennedy et al (1987) demonstrated that tolerance to volatile 2-tridecanone in the egg stage of Helicoverpa zea results in elevated levels of tolerance to the compound in newly hatched larvae. Although the mechanism of detoxification in this system is inferred, and not demonstrated, to be P450-related, the findings suggest that induced tolerance to allelochemicals may be critical to survival even before feeding begins.…”
Section: Discussionmentioning
confidence: 98%